Understanding the changes in practice patterns in ophthalmology following COVID-19 lockdown - Amit C Porwal (Indian Journal of Ophthalmology, 2021)
Purpose: Severe acute respiratory syndrome-Coronavirus 2 pandemic has brought the world to a halt. We performed a questionnaire-based survey to know more about these issues which affected them due to this pandemic and resultant lockdown. Methods: A questionnaire-based survey (53 questions) was conducted online among Indian ophthalmologists with a 2-week response time. The invitation to participate was also circulated widely among various ophthalmologists as members on different social media platforms and emails. It was mandatory to answer all the questions in the questionnaire to make it a valid response. Results: A total of 903 responses were received across the country. A majority of these responses, 403 (44.6%), were from private practitioners. Almost 876 (97%) of the responders had either kept the daily working hours as same as pre-COVID-19 era or had reduced the actual working hours. Overall, 547 (60.6%) responders did not downsize their staff and 569 (63%) did not reduce the staff salary. Consultation charges were not revised by a majority (659, 73%) of responders. Total of 663 (73.4%) were following the appointment system and 702 (77.7%) responders had reduced the number of patients to less than 6 an hour. Only 106 (11.7%) were doing a mandatory RT-PCR test before surgery, whereas 567 (62.8%) did on the basis of suspicious symptoms. Conclusion: Our survey gives valuable inputs regarding the changes made by different ophthalmologist groups during the times of COVID-19 and lockdown.